Philosophical dimensions of cultural policy - Guzhva, Alla (Filosofiya osvity. Philosophy of Education, 2024)
Against the background of Russia’s full-scale war against Ukraine, the question of an effective cultural policy that would support national identity, contribute to the purification of consciousness from propaganda myths and preserve the heritage of Ukrainian culture is becoming more acute. Since cultural policy is related to both aesthetic-artistic and cultural-anthropological dimensions of social life, in order to identify the effective influence of cultural policy on dominant social practices, it is necessary to find out the universal principles of its functioning. The purpose of this article is to identify the relevant philosophical and methodological basis of cultural policy for modern Ukrainian realities. Based on the fundamental ideas of Richard Rorty’s pragmatic philosophy and his analysis of cultural policies, the generally accepted nature of the inferential approach to social reality on the part of individual social groups was ascertained. The variability of cultural policy depending on the type of social organization community/society is demonstrated. In small social groups of the authoritarian type, social epistemological authority is mediated by the individual preferences of the leader of this group, so the tools of cultural policy are weak (patriarchal family, religious or political sect). An authoritarian or totalitarian mass society shows a high propensity for linguistic practices of propaganda, which can be seen as an extreme distorted form of cultural politics. In democratic societies, cultural policy is able to harmonize social life, improving its practices and building a value-symbolic world that constitutes culture in a broad sense. The social institute of education has all the tools, including digital ones, to shape the necessary social practices and educate a critical thinker who is able to generate conceptual knowledge, i.e. see relationships and be aware. Openness in decision-making, interaction of expert groups, public discussions are necessary elements for an effective cultural policy, which should be different from “cultural management”. Creative cultural industries play an important role in modern popular culture societies, and these industries significantly strengthen the economic component of social life. Public projects and initiatives effectively help to preserve Ukrainian culture, influence the level of awareness of Ukrainians and the economic well-being of our country.